2019
DOI: 10.32404/rean.v6i1.2403
|View full text |Cite
|
Sign up to set email alerts
|

Doses De Nitrogênio No Desenvolvimento De Mudas Altas De Maracujá-Amarelo

Abstract: RESUMOCom a disseminação do vírus do endurecimento dos frutos do maracujazeiro amarelo, surge a necessidade de produção de mudas maiores e mais vigorosas. Atualmente, há carência de informações sobre os aspectos nutricionais na formação de mudas com qualidade; desta forma, objetivou-se avaliar doses de nitrogênio (N) no desenvolvimento de mudas altas de maracujá amarelo. O delineamento experimental foi em blocos casualizados, com cinco tratamentos e cinco repetições. Os tratamentos foram compostos por doses de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…present in the soil 12.1 g dm -³, different from the present experiment that studied N dose in soil with higher O.M., 31.0 g dm -³. Bertani et al (2019) also observed the effect of the N dose increase in the PSD as well as in the PSL in advanced passion fruit seedlings. N influence on the PSD was verified in the evaluations at 60, 75, 90 days after the emergency (DAE), while at 45 DAE was not significant.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…present in the soil 12.1 g dm -³, different from the present experiment that studied N dose in soil with higher O.M., 31.0 g dm -³. Bertani et al (2019) also observed the effect of the N dose increase in the PSD as well as in the PSL in advanced passion fruit seedlings. N influence on the PSD was verified in the evaluations at 60, 75, 90 days after the emergency (DAE), while at 45 DAE was not significant.…”
Section: Resultscontrasting
confidence: 99%
“…However, although nitrogen (N) is the most extracted nutrient and the second most exported (HAAG et al, 1973;MATTAR et al, 2018) the recommended N amount for the crop varies between 94 and 235 kg ha -1 year -1 (RIPADO, 2010;MIYAKE et al, 2018). In addition, studies showed variable responses on N effect on fruit quality as well as nutritional studies in area with the presence of HFV, the performance evaluation of advanced seedlings in the field on N doses effect and its correlation with productivity are scarce (AULAR et al, 2014;MIYAKE et al, 2018;BERTANI et al, 2019). This lack of information hinders the elaboration of a precise recommendation to the rural producer, which can harm the activity productivity recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tall seedlings, for example, improves the quality of passion fruit when compared to conventional seedling planting (Santos et al, 2017a). Besides, this management technique also helps in controlling the fruit-hardening virus (Bertani et al, 2019). The highest plant height values found in the present study were 20.18 and 17.30 cm for seedlings produced with about 60% cattle manure or Organomais, respectively, added to the commercial substrate.…”
Section: Resultsmentioning
confidence: 55%
“…Santos et al (2011) evaluating different sources of N (ammonium sulfate, ammonium nitrate and urea) in the initial growth of yellow passion fruit plants, observed that the plants obtained very close values with SPAD index of 56.36, 57.17 and 59.02 for chlorophyll content. Bertani et al (2019) evaluating the feasibility of using the SPAD index as indicative of the nutritional status of plants in relation to nitrogen, observed to be a good index, since they presented approximate values of nitrogen content.…”
Section: Discussionmentioning
confidence: 99%